Wikis supporting research workshops in higher education - Rodríguez Hidalgo, Roberto Carlos; Torres Alfonso, Aida María; Zhu, Chang; Questier, Frederik (My University, 2011)
This paper reports the results of a pilot study conducted on a Cuban Higher Education setting. A classroom of twenty students of the Sciences of Information career at Central University “Marta Abreu” of Las Villas (UCLV) was inquired during the use of a wiki tool supporting a research workshop in the course of Databases Theory (DBT). The purpose of this study is to test the following hypotheses: (1) the collaboration supported by social software reinforces the peer relationships among the students of the class and (2) improves the time efficiency of the students and instructors (stakeholders) participating in these collaborative activities. A survey and several interviews were conducted to gather data about the social network the students formed for studying DBT, and about the time they spent on that. The results of these instruments were contrasted with the results of an observation conducted during the collaborative activities. The data of the students' achievements and social network state using the wiki tool were compared to similar data from other two precedent, non-wiki-supported research workshops. The use of the wiki tool was found effective to reinforce the peer learning relationships, and consequently, to improve their achievements on the subject. Finally, the time spent for accomplishing the collaborative learning activities did not decrease significantly during the use of the social software.
Wikis supporting research workshops in higher education. Prospective use in Cuban universities
Keywords: Collaboration; Colaboración; Cuban higher education; Cuba; Educación superior; Databases; Bases de datos; Sciences of Information career; Ciencias de la información; Social software; Software social; Web 2.0; Collaborative learning; Aprendizaje colaborativo; Computer aided instruction; Enseñanza asistida por computador; Graphs theory; Teoría de grafos; Networked learning; Aprendizaje en red; Peer learning relationships; Relaciones de aprendizaje; Research workshops; Seminarios investigativos; Social networking (online); Socialización en redes digitales; Social networks analysis; Análisis de redes sociales; Teaching and learning process; Proceso de enseñanza y aprendizaje; Herramientas wiki